Life-cycle assessment of oil recovery using dimethyl ether produced from green hydrogen and captured CO2 - R. Farajzadeh; N. Khoshnevis; D. Solomon; S. Masalmeh; J. Bruining (Scientific Reports)
Abstract Hydrocarbon fuels are widely recognized as significant contributors to climate change and the rising levels of CO2 in the atmosphere. As a result, it is crucial to reduce the net carbon intensity of energy derived from these fuels. This study explores the feasibility of using dimethyl ether (DME), produced through the hydrogenation of CO2, as a low-carbon method for generating electricity from hydrocarbon fuels. The proposed approach involves capturing the emitted CO2 during combustion and utilizing it to produce the necessary DME in a closed cycle. It is shown that for a mature reservoir in the Middle East, this method can mitigate approximately 75% of the CO2 emissions released from burning the produced oil. By incorporating zero-carbon electricity throughout the process, the total abatement of CO2 can reach 85%. Furthermore, the study highlights the importance of improving the DME utilization factor (bbl-oil/tDME). By optimizing this factor, high abatement rates can be achieved. However, it is important to note that implementing this method comes with a high exergetic cost. During a certain period in the field’s lifetime, the invested energy exceeds the energy produced. The stages with the highest exergy consumption are CO2 capture and hydrogen production.